2012
DOI: 10.1258/ijsa.2009.009198
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ceftriaxone for uncomplicated gonorrhoea: a meta-analysis of randomized controlled trials

Abstract: We conducted a systematic review and meta-analysis of ceftriaxone for treatment of uncomplicated gonorrhoea compared with four other antibiotics. Thirteen randomized controlled trials (RCTs) totalling treatment of 2557 patients with uncomplicated gonorrhoea were included. Statistically significant differences were observed in side-effects, which were increased after ceftriaxone 250 mg versus cefotaxime 500 mg (odds ratio [OR] 1.87; 95% confidence interval [CI] 1.14-3.08). Cure rates of ceftriaxone 250 mg were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…[34] Although the majority of the circulating gonococcal isolates in the US have a ceftriaxone MIC <0.03 µg/mL, there are no randomized controlled trials (RCT) comparing the efficacy of varying doses of ceftriaxone in contemporary times. A recent meta-analysis reviewed RCTs which compare ceftriaxone to other antimicrobials,[35] concluded that 250mg of intramuscular ceftriaxone is superior to 400mg oral cefixime, 2g intramuscular spectinomycin and 500mg of cefotaxime.…”
Section: Evidence For Current Recommended Treatment Regimensmentioning
confidence: 99%
“…[34] Although the majority of the circulating gonococcal isolates in the US have a ceftriaxone MIC <0.03 µg/mL, there are no randomized controlled trials (RCT) comparing the efficacy of varying doses of ceftriaxone in contemporary times. A recent meta-analysis reviewed RCTs which compare ceftriaxone to other antimicrobials,[35] concluded that 250mg of intramuscular ceftriaxone is superior to 400mg oral cefixime, 2g intramuscular spectinomycin and 500mg of cefotaxime.…”
Section: Evidence For Current Recommended Treatment Regimensmentioning
confidence: 99%
“…cefixime 800 mg × 1 plus azithromycin 1 g × 1. Mainly early evidence indicated that cefixime 800 mg × 1 was safe and effective in treating gonorrhoea [ 66 , 69 , 71 , 72 , 75 , 76 ]. Pharmacodynamic studies and/or simulations have also shown that, compared to 400 mg × 1, 800 mg of cefixime (particularly administered as 400 mg × 2, 6 hours apart) substantially increases the f T >MIC of cefixime [ 22 , 52 ].…”
Section: Reviewmentioning
confidence: 99%
“…Treatment for cure of CT and NG is effective (> 95% for CT and > 85% for NG, if uncomplicated infection) if properly adhered to, and will reduce the risk for complications of the infections as described above. Antibiotics typically used to treat CT and NG (described in Additional file 2) are quite commonly (15-25%) associated with mild adverse effects (AEs) including diarrhea, vomiting, constipation, abdominal pain, vertigo, fatigue and headache [44, 45]. The majority of AEs from CT and NG treatment are gastrointestinal in nature and may be severe in some cases particularly for NG where combination treatment or higher-dose single agents are used (e.g., 2 vs. 1 g dose of azithromycin).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of AEs from CT and NG treatment are gastrointestinal in nature and may be severe in some cases particularly for NG where combination treatment or higher-dose single agents are used (e.g., 2 vs. 1 g dose of azithromycin). Very rarely (< 1 in 1000 people treated), people will have serious adverse drug reactions leading to hospitalization, from severe allergy to the antibiotic, Clostridium difficile colitis (possibly with life-threatening diarrhea), liver toxicity, heartbeat irregularities (from azithromycin although mainly for multi-day doses in specific patient subgroups), or other organ complications [4448].…”
Section: Introductionmentioning
confidence: 99%